Effect of a raw saponin extract on ruminal microbial population and in vitro methane production with star grass (Cynodon nlemfuensis) substrate - Galindo, Juana; González, Niurca; Luiz Abdalla, A.; Alberto, Mariem; Lucas, R. C.; Dos Santos, K. C.; Santos, M. Regina; Louvandini, P.; Moreira, O.; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2016)
An experiment was conducted under in vitro conditions for determining the effect of a raw saponin extract on the ruminal microbial population and in vitro methane production with star grass (Cynodon nlemfuensis) substrate. Treatments were designed according to the quantity of saponin extract: 1) control, without saponins, 2) 0.6 %, 3) 1.2 % and 4) 1.8 % of the DM of raw saponin extract. The basal diet was star grass (C. nlemfuensis). The saponin extract was obtained from Sapindus saponaria fruit and its saponin content was of 139.5 mg, equivalent of diogenin.mL-1. There was a reduction in protozoa population, regardless the saponin level. Its effect on the main cellulolytic bacteria, determined by PCR-RT, showed that the amount of Fibrobacter succinogenes was not modified while the values of Ruminococcus albus were 25.92; 26.72; 25.2 and 22.35 CT for the levels 0; 0.6; 1.2 and 1.8 %, respectively. The acetic acid concentration was not modified by the saponins; the propionic was reduced with 1.2 % inclusion. The concentration of valeric acid was 0.68; 0.62; 0.52 and 0.49 mmol.L-1 for 0, 0.6; 1.2 and 1.8 % of saponin extract, respectively. Saponins increased methanogenic representation and methane production. It is concluded that the saponin extract modulates the fermentative process on reducing protozoa, does not modify the presence of F. succinogenes and decreases that of R. albus, probably due to the fact that both utilize the same resource, space and carbon source in the rumen. The quantity of methanogens was higher with 1.2 and 1.8 % coinciding with the highest methane production. Key words: Fibrobacter succinogenes, Ruminococcus albus, star grass, methanogens